General Effects of Fluorine and Its Compounds on Livestock. - Goyibnazarov Kilich; Salimov Yunus (Research Parks Publishing LLC, 2021)
The article studies the pathological processes that occur as a result of the specific properties of fluorine and its compounds, which are wastes of the Tajik aluminum plant, in the general effects on the organism of large horned animals.